Design and Development of a Smart Trash Bin to Minimize Odor from Household Waste Based on the Internet of Things - Mohd Abdul Ghaffar; David HL, David; Kim Leah; Mansyur (Ceddi Journal of Information System and Technology (JST), 2024)
The problem that occurs is that household waste continues to increase along with the development of population and the number of increasingly dense settlements. The existence of this household waste is of concern to the community and the government because it can cause various negative impacts. Based on the results of observations of the existing trash cans, the accumulation of household waste is the source of this unpleasant odor. Smell is connoted as something that tends to disturb comfort, and gives the impression of being unclean and the like, such as fishy, rotten, urine, rancid, and so on. The smell of burning garbage is also dangerous because it contains H2 which reduces the amount of oxygen in the air. This study aims to prevent the occurrence of unpleasant odors from garbage. The tool will be designed using the NodeMCU microcontroller with website-based monitoring and Whatsapp notifications automatically when the trash can is full and automatic deodorizing powder spraying according to the concentration of gas released by the stench. This study uses the Experimental and Comparative Testing method in designing an IoT-based Smart Trash Bin tool and conducting tests on the built system and comparing the test results with the expected system. The results of this study indicate that the Smart Trash Bin tool can work and function as expected, namely being able to minimize the unpleasant odor emitted by the trash can and being able to monitor the sprinkling of deodorizing powder, the status of the height of the trash can and can provide notifications both automatically and manual to officers through the website.